Development of Learning Trajectory for Project-Based Learning (PjBL) Model to Construct Foundational Literacies for Elementary School Students - Rohman, Fatkhur; Astuti, Nelly; Maryam, Eka; Erni, Erni; Azzahra, Mia; Hermawan, Jody Setya (SCOPE: Journal of English Language Teaching, 2024)
Learning trajectories oriented towards Foundational Literacies such as reading literacy, communication skills, and critical thinking need to be developed to prepare learners to face the changes of the 21st century. Learning access in Phase C requires the student to have the ability to adapt to the purpose and social context, show an interest in the text, and be able to understand, process, and interpret information. While the thinking stage of the SD pupil according to Piaget's theory, is in the concrete operational stage, therefore learning in Phase C is considered difficult for SD pupils. Teachers have not fully implemented the development of learning actively, and creatively in involving students and have not used various learning models based on the character of the learning material. That affects the achievement of the Foundational Literacies of the lower pupils. This research aims to develop a learning trajectory model of PjBL that can build the Foundational Literacies of the students in studying a topic set in Phase C. Design research used in this research comprises three stages, namely: (1) preparing for the experiment; (2) design experiment; and (3) retrospective analysis. The results of the implementation of the first prototype give a significant impact on the change in the Foundational Literacies before and after learning, but when referring to the criteria of achievement of the learning objective holistically is still in fairly good interpretation. Re-development of the learning trajectory resulting in prototype II. The implementation of the second prototype achieved an average N-Gain score of the experimental class of 78.31% and the control class has a score of 54.20%, the results of this study indicate that the Learning Trajectory for the PjBL Model effectively imply building Foundational Literacies.